2008
DOI: 10.1021/la701760s
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Surface pK of Carboxylic- and Amine-Terminated Alkanethiols Using Surface Plasmon Resonance Spectroscopy

Abstract: When using self-assembled monolayers (SAMs) with ionizable functional groups, such as COOH and NH2, the dissociation constant (pKd) of the surface is an important property to know, since it defines the charge density of the surface for a given bulk solution pH. In this study, we developed a method using surface plasmon resonance (SPR) spectroscopy for the direct measurement of the pKd of a SAM surface by combining the ability of SPR to detect the change in mass concentration close to a surface and the shift in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
112
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(126 citation statements)
references
References 34 publications
13
112
1
Order By: Relevance
“…A pK a of 6.5 was reported for NH 2 -(CH 2 ) 11 -SH monolayers on Au and a pK a of 7.4 for COOH-(CH 2 ) 11 -SH monolayers on Au by surface plasmon resonance spectroscopy. 24 For the shorter chain length we used in the present work, Marmisolle et al recently reported a pK a of NH 2 -thiol (6-amino-1-hexanethiol) of approximately 7 for monolayers on Au measured by titration and impedance spectroscopy. 25 Thus, we can reasonably assume that our patterns have similar pK a 's, which means that, in terms of their ionization state, we would expect predominantly positively charged NH 3 þ -groups at low (acidic) pH and predominantly neutral NH 2 -groups at high (basic) pH.…”
mentioning
confidence: 88%
“…A pK a of 6.5 was reported for NH 2 -(CH 2 ) 11 -SH monolayers on Au and a pK a of 7.4 for COOH-(CH 2 ) 11 -SH monolayers on Au by surface plasmon resonance spectroscopy. 24 For the shorter chain length we used in the present work, Marmisolle et al recently reported a pK a of NH 2 -thiol (6-amino-1-hexanethiol) of approximately 7 for monolayers on Au measured by titration and impedance spectroscopy. 25 Thus, we can reasonably assume that our patterns have similar pK a 's, which means that, in terms of their ionization state, we would expect predominantly positively charged NH 3 þ -groups at low (acidic) pH and predominantly neutral NH 2 -groups at high (basic) pH.…”
mentioning
confidence: 88%
“…The two SAM surfaces used in this study were represented by a hydrophobic, methyl-terminated SAM (CH 3 -SAM) and a hydrophilic, negatively charged carboxylic acid-terminated SAM (COOH-SAM). These surfaces were constructed using methods that Latour and coworkers [16][17][18][19][20][21][22] and others [23][24][25][26][27][28] have used in several previous simulation studies involving SAMs. The SAM surfaces were each represented as consisting of functionalized alkyl chains of 10 carbons, including the functional group carbon.…”
Section: Model Molecular Systemsmentioning
confidence: 99%
“…The SAM surfaces were each represented as consisting of functionalized alkyl chains of 10 carbons, including the functional group carbon. 50% of the carboxylic acid groups of the COOH-SAM were deprotonated, as appropriate for the experimentally determined pK a value of 7.4 [22]. To maintain neutrality of the systems with the COOH-SAM, 60 additional Na ?…”
Section: Model Molecular Systemsmentioning
confidence: 99%
“…For this reason, in cases where there are charged groups on the surface, atomic force microscopy has been used to determine the surface potential and through this, the area density of surface charges [68]. Similarly, for SAMs where the composition is known a priori, but can also be confirmed with XPS, surface plasmon resonance (SPR) can measure the pKa of the surface functional groups and help in modelling the correct area density of charges under different pH conditions [69].…”
Section: Experimental Target Data and Validation Datamentioning
confidence: 99%